Famille contre contrat: une perspective hégélienne (Revista Eletrônica Estudos Hegelianos, 2022)
Hegel’s theory of the family is usually seen as a theory grounded in love, as opposed to a model of justice based on individual rights. According to Hegel, the family, as one moment of ethical life, cannot be reduced to the mere commonality of personality formed by mere individual rights, a theoretical form represented by Kant. But Hegel’s emphasis on ethical love in the family is not equal to an appeal to a higher ethical ideal which blurs the basic rights claims of the individual in family. Rather, by emphasizing the irreducibility of the family to contract, especially by showing that the personal right does not apply to the domain of freedom of immanence of personality, Hegel demonstrates in fact the fundamental conditions of individual freedom.